Memaknai Bahasa Visual pada Ilustrasi Bergambar Soeharto di Sampul Muka Majalah Tempo - Danendro Adi (Humaniora, 2014)
Illustration on publication media has become a form to deliver message visually that is more powerful than written message. Illustration is able to build readers perception and attention. Illustration on the cover of a magazine needs the writer and the artist synergy in order to create artwork that deliver messages in a certain visual language at the same time gives identity to the magazine. This paper will discuss the illustrations and visual language used and the extent of utilization and the impact of the illustrations of the readers and the media in which the illustration shown. Illustrations of the former President Soeharto on the cover of Tempo magazine since 1998 edition, after his retirement until his death in 2008 become the case study and the cover of the magazines during the New Order era as the comparison. The research method used in this study is qualitative research methods including data collection in the form of a literature study and interviews, followed by analyzing the data findings. This study should obtain a clearer picture on how illustrations affect the news media and the relation to the audience’s perception about the character in the illustration.